Soviet robots in the solar system mission technologies and discoveries - Huntress, JR., Wesley T. (Wesley Theodore); SpringerLink (Online service). (New York, NY Springer New York Imprint: Springer, 2011)
The Soviet robotic space exploration program began in a spirit of bold adventure and technical genius. It ended after the fall of the Soviet Union and the failure of its last mission to Mars in 1996. Soviet Robots in the Solar System chronicles the scientific and engineering accomplishments of this enterprise from its infancy to its demise. Each flight campaign is set into context of national politics and international competition with the United States. Together with its many detailed illustrations and images, Soviet Robots in the Solar System presents the most detailed technical description of Soviet robotic space flights provides a unique insight into programmatic, engineering, and scientific issues covers mission objectives, spacecraft engineering, flight details, scientific payload and results describes in technical depth Soviet lunar and planetary probes.
Illustrations -- Author's Preface -- Acknowledgments -- Part 1: The pieces: people, institutions, rockets and spacecraft -- Chapter 1: Space race -- Chapter 2: Key players -- Chapter 3: Key institutions -- Chapter 4: Rockets -- Chapter 5: Spacecraft -- Part II: Putting the pieces together: flying to the Moon, Venus, and Mars -- Chapter 6: Breaking free of Earth -- Chapter 7: Launching to Mars and Venus -- Chapter 8: New spacecraft, new failures -- Chapter 9: Three more years of frustration -- Chapter 10: Finally success at the Moon and Venus, but Mars eludes -- Chapter 11: Robotic achievements in the shadow of Apollo -- Chapter 12: Landing on the Moon, Venus, and Mars -- Chapter 13: Closeouts on a Venus spacecraft, a Moon rocket, and desperation at Mars -- Chapter14: Turning from the Moon and Mars to Venus -- Chapter 15: Repeating success at Venus -- Chapter 16: Back to Venus again -- Chapter 17: And back to Venus yet again -- Chapter 18: The International Comet Halley campaign -- Chapter 19: Another try at Mars and its moon Phobos -- Chapter 20: The last gasp: Mars-96 -- Chapter 21: The Soviet lunar and planetary exploration legacy -- Appendices -- Bibliography -- Index.
Electronic reproduction.
Keywords: Space robotics -- Soviet Union; Space robotics -- Russia (Federation).; Outer space -- Exploration -- Soviet Union; Outer space -- Exploration -- Russia (Federation).; Astronautics -- History. -- Soviet Union; Electronic books